2013
DOI: 10.5458/jag.jag.jag-2012_008
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Resistant Starch during Acid Hydrolysis of High-amylose Corn Starch

Abstract: Four types of corn starch (waxy corn starch (WC), normal corn starch (NC), high-amylose corn starch class 5 (HAC class 5) and high-amylose corn starch class 7 (HAC class 7)) were hydrolyzed with 1.5% hydrochloric acid and the resistant starch (RS) content was measured. The acid-hydrolyzed HAC class 5 and class 7 show significantly higher RS content. The change in RS content, X-ray crystallinity, molecular size distribution, thermal property and appearance of HAC class 7 after up to 100 h acid hydrolysis were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
2
20
0
4
Order By: Relevance
“…In 1 study, using H7 corn starch, 1% HCl was added to a starch slurry containing up to 35% solids and hydrolysis was carried out at 45 °C for up to 78 h. After in vitro enzyme analysis was completed on the 78 h samples, it was found that there was no statistically significant increase in RS content (Brumovsky and Thompson ). This same trend was noted by Ozturk and others () who also noted that acid treatment prior to autoclaving also had negligible effect on final RS levels of H5 and H7 corn starches, however, their hydrolysis times were only 3 h. Nagahata and others () subjected waxy, normal, and H5 and H7 corn starches to 24 h acid hydrolysis (by HCl). The RS content was determined using an MRSK and the RS content of the waxy corn starch decreased by 0.3%, however, the other starches increased by 6.7%, 17.6%, and 28.2%, respectively.…”
Section: Chemical Modifications For Increasing Rs Contentsupporting
confidence: 75%
See 1 more Smart Citation
“…In 1 study, using H7 corn starch, 1% HCl was added to a starch slurry containing up to 35% solids and hydrolysis was carried out at 45 °C for up to 78 h. After in vitro enzyme analysis was completed on the 78 h samples, it was found that there was no statistically significant increase in RS content (Brumovsky and Thompson ). This same trend was noted by Ozturk and others () who also noted that acid treatment prior to autoclaving also had negligible effect on final RS levels of H5 and H7 corn starches, however, their hydrolysis times were only 3 h. Nagahata and others () subjected waxy, normal, and H5 and H7 corn starches to 24 h acid hydrolysis (by HCl). The RS content was determined using an MRSK and the RS content of the waxy corn starch decreased by 0.3%, however, the other starches increased by 6.7%, 17.6%, and 28.2%, respectively.…”
Section: Chemical Modifications For Increasing Rs Contentsupporting
confidence: 75%
“…The RS content was determined using an MRSK and the RS content of the waxy corn starch decreased by 0.3%, however, the other starches increased by 6.7%, 17.6%, and 28.2%, respectively. These increases were relative to the amount of starch left behind after acid hydrolysis, as in a long‐term study (100 h of hydrolysis) using H7, total crystallinity and RS increased, however, starch yield along with the amount of high‐molecular‐weight starch fragments decreased (Nagahata and others ). The acid predominantly hydrolyzes the amorphous regions, leaving behind the crystalline regions that both offer higher resistance to acid and enzyme attack.…”
Section: Chemical Modifications For Increasing Rs Contentmentioning
confidence: 95%
“…The extent of hydrolysis of a starch granule is dependent on the acid type, acid concentration, and hydrolysis time. The susceptibility of native starch granules to acid hydrolysis also depends on factors such as 1) the presence of pores on the granule surface, 2) the granule size (Vasanthan and Bhatty 1996), 3) the amount of a-(1→6) linkages (Inouchi et al 1987), 4) the amount and nature of lipid-complexed amylose chains (Jayakody and Hoover 2002), 5) the extent to which amylose chains are cocrystallized with amylopectin and/or are buried within the crystalline lamellae (Vamadevan et al 2014), 6) the packing density of amylose chains within the amorphous regions (Hoover and Manuel 1996), and 7) the polymorphic type of starch present (Jane et al 1997;Nagahata et al 2013).…”
mentioning
confidence: 99%
“…The chemical processes, in turn, promote the modification of starch granules by linterization, acetylation, phosphorylation, oxidation, hydroxypropylation, esterification and the combination of these treatments …”
Section: Sources Of Renewable Materialsmentioning
confidence: 99%
“…40 The chemical processes, in turn, promote the modification of starch granules by linterization, acetylation, phosphorylation, oxidation, hydroxypropylation, esterification and the combination of these treatments. 41 Linterization consists of an acid treatment to remove crystalline and amorphous regions, which will result in more resistant starch crystals. While hydroxypropylation uses functional chemical reagents that alters the properties of the polymer and oxidation uses an oxidizing agent to form new hydroxyl groups.…”
Section: Starchmentioning
confidence: 99%